Phenol-Soluble Modulin Toxins of Staphylococcus haemolyticus - Da, Fei; Joo, Hwang-Soo; Cheung, Gordon Y. C.; Villaruz, Amer E.; Rohde, Holger; Luo, Xiaoxing; Otto, Michael (Frontiers in Cellular and Infection Microbiology, 2017)
Coagulase-negative staphylococci (CoNS) are important nosocomial pathogens and the leading cause of sepsis. The second most frequently implicated species, after Staphylococcus epidermidis, is Staphylococcus haemolyticus. However, we have a significant lack of knowledge about what causes virulence of S. haemolyticus, as virulence factors of this pathogen have remained virtually unexplored. In contrast to the aggressive pathogen Staphylococcus aureus, toxin production has traditionally not been associated with CoNS. Recent findings have suggested that phenol-soluble modulins (PSMs), amphipathic peptide toxins with broad cytolytic activity, are widespread in staphylococci, but there has been no systematic assessment of PSM production in CoNS other than S. epidermidis. Here, we identified, purified, and characterized PSMs of S. haemolyticus. We found three PSMs of the β-type, which correspond to peptides that before were described to have anti-gonococcal activity. We also detected an α-type PSM that has not previously been described. Furthermore, we confirmed that S. haemolyticus does not produce a δ-toxin, as results from genome sequencing had indicated. All four S. haemolyticus PSMs had strong pro-inflammatory activity, promoting neutrophil chemotaxis. Notably, we identified in particular the novel α-type PSM, S. haemolyticus PSMα, as a potent hemolysin and leukocidin. For the first time, our study describes toxins of this important staphylococcal pathogen with the potential to have a significant impact on virulence during blood infection and sepsis.